2014
DOI: 10.15252/emmm.201404168
|View full text |Cite
|
Sign up to set email alerts
|

R‐flurbiprofen attenuates experimental autoimmune encephalomyelitis in mice

Abstract: R-flurbiprofen is the non-cyclooxygenase inhibiting R-enantiomer of the non-steroidal anti-inflammatory drug flurbiprofen, which was assessed as a remedy for Alzheimer's disease. Because of its anti-inflammatory, endocannabinoid-modulating and antioxidative properties, combined with low toxicity, the present study assessed R-flurbiprofen in experimental autoimmune encephalomyelitis (EAE) models of multiple sclerosis in mice. Oral R-flurbiprofen prevented and attenuated primary progressive EAE in C57BL6/J mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 75 publications
2
45
0
Order By: Relevance
“…Alternatively, intraperitoneally co-administered nanoparticles formulated with myelin antigen and aryl hydrocarbon receptor ligands promoted tolerogenic DCs and mitigated EAE, with expansion of T reg cells [52]. In testing treatment strategies for EAE, preventative/prophylactic treatment has been used when the treatment agents are administered to animals before EAE disease induction, therapeutic treatment is applied when agents are given to animals after appearance of clinical EAE disease signs, and semi-therapeutic regimen is used when treatment agents are administered to animals after EAE disease induction but before clinical disease signs [51, 53]. The combinatorial multi-factor dMP treatment investigated here offers the advantage of a subcutaneous localized administration, as opposed to systemic administration, with low-dose, localized, controlled release of specific factors designed to be retained at the injection site.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, intraperitoneally co-administered nanoparticles formulated with myelin antigen and aryl hydrocarbon receptor ligands promoted tolerogenic DCs and mitigated EAE, with expansion of T reg cells [52]. In testing treatment strategies for EAE, preventative/prophylactic treatment has been used when the treatment agents are administered to animals before EAE disease induction, therapeutic treatment is applied when agents are given to animals after appearance of clinical EAE disease signs, and semi-therapeutic regimen is used when treatment agents are administered to animals after EAE disease induction but before clinical disease signs [51, 53]. The combinatorial multi-factor dMP treatment investigated here offers the advantage of a subcutaneous localized administration, as opposed to systemic administration, with low-dose, localized, controlled release of specific factors designed to be retained at the injection site.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The fraction inverted in the present study was estimated by application : 13 The enantioselective measurement of the plasma levels of both enantiomers permits assessment of the nature of the inversion process. [8][9][10] The fraction inverted in the present study was estimated by application : 13 The enantioselective measurement of the plasma levels of both enantiomers permits assessment of the nature of the inversion process.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The rat seems to have an inversion profile similar to humans. 8 This renders RF a potentially orally active, clinically well-tolerated agent for the therapeutic treatment of relapsing-remitting MS. To gain a more comprehensive preclinical assessment of its pharmacokinetic behavior for pharmacodynamic studies in the present study, we investigated the inversion of RF to SF and vice versa in different rodent strains, commonly used in EAE studies. 7 In the mouse, fractional inversion of oral RF to SF is 15% to 22%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that other behaviors were associated with EAE, including mechanical allodynia (reflecting neuropathic pain), decreased voluntary wheel running (reflecting fatigue and motor impairments), and decreased social exploration (reflecting anxiety). These symptoms are rarely assessed in rodent models, despite their frequent association with MS. Assessment of nociceptive hypersensitivity in relapsing remitting models is limited, but several studies have demonstrated pharmacological reversal of allodynia (Khan et al, 2014; Lu et al, 2012; Lynch et al, 2008; Ramos et al, 2010; Schmitz et al, 2014; Sloane et al, 2009; Thibault et al, 2011; Tian et al, 2013). While anxiety behaviors are a known feature in EAE models (Acharjee et al, 2013; Peruga et al, 2011; Pollak et al, 2000), only two studies have evaluated therapeutic modulation (Di Prisco et al, 2014; Haji et al, 2012).…”
Section: Discussionmentioning
confidence: 99%